Anestesia peribulbar guiada por ultrassom com diferentes volumes de ropivacaína a 1 por cento associada ou não ao bicarbonato de sódio em cães - Wagatsuma, Juliana Tessália [UNESP] (2016)
Seven dogs were subjected to inhalation anesthesia with isoflurane to allow the realization of peribulbar block, with lower single puncture, guided by ultrasound with 1% ropivacaine, and thus prove the effectiveness of this blocking technique guided in reducing anesthetic volume of ropivacaine 1%, and evaluate possible potentiating effects such as reducing the latency and anesthetic volume used and ophthalmic complications associated with the anesthetic alkalinization with sodium bicarbonate 0,33%. We evaluated two different volumes of 1% ropivacaine (0.2 ml / kg and 0.1 ml / kg) with or without sodium bicarbonate to 0.33% which when added to anesthetic raised the pH of the solution anesthetic to 6.0. Once performed peribulbar block, with lower single puncture guided by ultrasound time required to place the centralization of the eye bulb was timed, and the animals remained anesthetized for the measurement of intraocular pressure was carried out immediately and 15 minutes after blockade and completed this measurement, anesthesia was terminated. With dogs the following parameters already awake were evaluated intraocular pressure, pupil size, the duration and intensity of motor block, sensory (performed by esthesiometry corneal with esthesiometer Cochet and Bonnet), and observation of ophthalmic complications as chemosis, conjunctival hyperemia, subconjunctival hematoma, pruritus, and ocular secretion resulting from the anesthetic technique or employee drug. Statistical analyzes were conducted with the free software Rstudio. nonparametric variables, ordinal variables and categorical variables were evaluated using the statistical test ANOVA type or ATS. Parametric continuous variables were assessed by linear mixed model for repeated measures. The Test Kendall Tau-b was used to verify possible correlations between variables. Aside from fotomotor reflex (G0,1: 30 (0-90) and G0,2: 150 (0-210 minutes), there was no significant difference between groups when compared to latency, intraocular pressure, pupil size, the durations and quality of sensory and motor block, and ophthalmic complications, but there was significant difference when comparing times within the same group for all variables. Thus it was concluded that among the evaluated volumes of 1% ropivacaine in the lock US peribulbar guided in dogs, there was a better clinical performance related to the intensity and duration of sensory and motor block, with a volume of 0.2 ml / kg. the addition of 0.33% NaHCO3 no added benefits, such as potentiation of action or reduction of latency anesthetic, but no significant ophthalmic complications directly related to its administration or the 1% ropivacaine.